Growth performance of Asian seabass Lates calcarifer (Bloch, 1790) stocked at varying densities in floating cages in Godavari Estuary, Andhra Pradesh, India - Ghosh, Shubhadeep; Megarajan, Sekar; Ranjan, Ritesh; Dash, Biswajit; Pattnaik, Phalguni; Edward, Loveson; Xavier, Biji (Indian Journal of Fisheries, 2016)
Present study was undertaken in Godavary Estuary, Andhra Pradesh for evaluation of the effect of three stocking densities on growth performance, survival and production of Lates calcarifer (Bloch, 1790) in floating cages and for optimisation of stocking density in cage farming. Seabass fingerlings having length and weight of 8.36±0.32 cm and 8.10±0.61 g respectively, were stocked in six cages (6 m dia; 3 m net depth) at three different stocking densities of 15, 30 and 45 nos. m-3 and their growth performance was monitored every fortnight for five months. All fishes were fed with chopped trash fish @ 8 - 12% of body weight. After 150 days of grow-out culture, seabass fingerlings reached 36.0±6.0 cm in length and 690.7±41.3 g in weight at density of 15 nos. m-3, 33.9±0.4 cm and 633.2±17.9 g at density of 30 m-3 and 30.2±0.4 cm and 465.0±21.2 g at density of 45 nos. m-3. Growth was allometric and did not differ with stocking density. Survival percentage was comparatively higher at lower (87.3%) and moderate (83.9%) stocking densities, while production was higher at moderate (1363.2 kg) and higher (1258.4 kg) stocking densities (p